(3GJMGa GdCOjH HLhGR ESJfGHI GdNWjHs - (3MSf Hf YeGQ GdeUQj GdTQfHdGdj GdMfaj , CHh GdHQcGJ,J (B1069 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdYHO GdYGLR GdPdjd MSf GdTQfHdGdi GdhaGi GdMfai s
(3BNQgG (B:s
(3ajUHM JbOeI HfaSg hJbOjeg ZjQg hGeG EPG TQY GdNWjH ai GdUdGI s
(3HgG fXGe GdJYbjHIs
(3jXf Efg HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B265 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B292s
Keywords: (3CUhd Gdabgs